2010
DOI: 10.1097/aco.0b013e328333b09b
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complications after oesophageal surgery

Abstract: The multifactorial nature of respiratory complications after oesophageal surgery may mean that a number of interventions are needed to have a detectable influence on outcome, much like a care bundle strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Patients with late ARDS had fewer ventilator-free days (median 17, interquartile range (IQR) 11-24), compared with early ARDS (median 27, IQR [18][19][20][21][22][23][24][25][26][27][28] and no ARDS (median 28, IQR [27][28]. The duration of intensive care stay was shortest in those without ARDS (mean 7.3 days, standard deviation () 5.4), longer with early ARDS (mean 12.1 days,  9.0) and longer still with late disease (mean 20.2 days,  8.0).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with late ARDS had fewer ventilator-free days (median 17, interquartile range (IQR) 11-24), compared with early ARDS (median 27, IQR [18][19][20][21][22][23][24][25][26][27][28] and no ARDS (median 28, IQR [27][28]. The duration of intensive care stay was shortest in those without ARDS (mean 7.3 days, standard deviation () 5.4), longer with early ARDS (mean 12.1 days,  9.0) and longer still with late disease (mean 20.2 days,  8.0).…”
Section: Resultsmentioning
confidence: 99%
“…83 Too little fluid could compromise perfusion of vital organs and surgical anastomoses, but fluid overload could lead to pulmonary edema and subsequent acute lung injury (ALI) (which carries a mortality rate of <50%), 52,84,85 or anastomotic edema and, therefore, leak. 86 Patients who have such postoperative complications but survive to hospital discharge have reduced long-term survival.…”
Section: Perioperative Fluid Managementmentioning
confidence: 99%
“…It has been demonstrated that pulmonary complications are the most common source of morbidity and mortality after esophagectomy 2,13 . Therefore, oral health care during the perioperative period is essential for the proper management of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding esophageal cancer, it has been reported that the most frequent problems associated with esophageal surgery were related to respiratory complications, which result in increased critical care stay, hospital stay and mortality 13 . In addition, Atkins and D'Amico 2 (2006) reported that pulmonary complications were the most common source of morbidity and mortality after esophageal resection.…”
Section: Introductionmentioning
confidence: 99%